Implementasi Kurikulum Pelatihan Geografi Kebencanaan Pada Siswa SMP Yaskitta Desa Hambalang Kecamatan Citeureup Kabupaten Bogor - Shalsadila, Azritamara; Hardi, Ode Sofyan; Munandar, Aris (Peneliti.net, 2024)
This study aims to determine the effectiveness of the implementation of the disaster geography training curriculum for junior high schools in increasing the understanding of Yaskitta Junior High School students about landslide disaster preparedness in Yaskitta Junior High School, Hambalang Village, Citeureup District, Bogor Regency. The research method used is a quasi-experimental design in the form of a One Group Pretest-Posttest Design. The population in this study is all students at SMP Yaskitta in Hambalang Village, totaling 155 students. The sample consists of seventh-grade students, amounting to 52 students, selected using simple random sampling. Junior high school students are chosen as representatives of the younger generation. Data collection techniques include observation, questionnaires, documentation, and literature review. Data analysis techniques include descriptive statistical analysis and inferential statistical analysis. Curriculum implementation is carried out outside of regular class hours or non-teaching activities.Based on the calculation of the average pretest and posttest scores, it can be concluded that the implementation of this curriculum is effective in improving students' understanding of disaster preparedness. The hypothesis testing results obtained from the t-test show a t-value of 12.25, with a degree of freedom (df) of 50. At a 5% significance level, the t-table value is 1.676. Therefore, the calculated t-value (12.25) is greater than the t-table value (1.676), leading to the rejection of the null hypothesis indicating that the curriculum implementation is not effective in improving the understanding of seventh-grade students about landslide disaster preparedness. The alternative hypothesis is accepted, indicating that the curriculum implementation is effective in improving the understanding of seventh-grade students about landslide disaster preparedness.